The Family in Medical Decisionmaking - Blustein, Jeffrey (The Hastings Center report, 1993)
Should the authority to make treatment decisions be extended to the competent patient's family? Neither arguments from fairness nor communitarian concerns justify such an infringement on patient autonomy.